Constitutional Legitimacy and Institutional Behavior of Political Parties in the 2024 Regional Elections: Legitimitasi Konstitusional dan Perilaku Kelembagaan Parpol dalam Calon Tunggal Pilkada 2024 - Rohmah, Elva Imeldatur (Jurnal Konstitusi, 2025)
Since the Constitutional Court’s Decision No. 100/PUU-XIII/2015, the prevalence of single-candidate contests in regional head elections (Pilkada) has increased markedly. This phenomenon presents constitutional and democratic dilemmas, generating a crisis of substantive legitimacy and weakening political competition. The pragmatic behavior of political parties and the weakness of their cadre-building systems further exacerbate the paucity of contestation. This study aims to examine the constitutional basis for the legitimacy of single candidates in Pilkada, assess the responsibility of political parties for the low level of competition, and identify normative alternatives to prevent the dominance of single candidates in local elections. It is a normative legal study employing three approaches: statutory, conceptual, and comparative. The findings indicate that, formally, single-candidate nominations are constitutionally valid; however, their substantive legitimacy is questionable due to the limited range of political choices and the underperformance of parties’ recruitment functions. Practices such as the wholesale capture of party endorsements by strong candidates and the dominance of party elites narrow the space for competition. To prevent this, regulatory reforms are needed, including strengthening cadre development, imposing an upper limit on party coalitions, and facilitating independent candidacies as a political alternative. In this way, local democracy can become more competitive, participatory, and substantive.